2012
DOI: 10.1161/strokeaha.111.644674
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar and Cerebral Autoregulation in Migraine

Abstract: Background and Purpose-Silent ischemic brain lesions frequently occur in migraine with aura and are most often located in cerebellar border zones. This may imply an impairment of cerebellar blood flow autoregulation. This study investigated the characteristics of interictal cerebellar autoregulation in migraine with and without aura. Methods-Thirty-four patients (nϭ17, migraine without aura; nϭ17, migraine with aura) and 35 age-and sex-matched controls were studied. Triple simultaneous transcranial Doppler mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…It has previously been reported that dCA is impaired in migraineurs [9], [18]. Müller et al studied 22 migraine patients and 33 healthy controls and found that dCA phase and gain appeared to be completely different in migraineurs compared with healthy controls [9].…”
Section: Discussionmentioning
confidence: 97%
“…It has previously been reported that dCA is impaired in migraineurs [9], [18]. Müller et al studied 22 migraine patients and 33 healthy controls and found that dCA phase and gain appeared to be completely different in migraineurs compared with healthy controls [9].…”
Section: Discussionmentioning
confidence: 97%
“…A higher gain indicates less dampening effects and thus poorer autoregulatory ability. 13 An example recording is shown in Figure 1. Autoregulation parameters in the MCA and PCA of pregnant study participants were compared with autoregulation parameters of 26 healthy nonpregnant women of similar age (29±7 years) who participated in a previous study.…”
Section: Methodsmentioning
confidence: 99%
“…Although further work is needed, these findings may explain why long-term hypertension was more frequent in the migraine with aura group in our study. 22 We suspected that there might be ethnic and racial factors in the association of migraines and hypertension, which could conceivably contribute to greater stroke risks in Blacks and Hispanics. Both hypertension and migraine are risk factors for silent brain lesions, both white matter hyperintensities and silent brain infarctions, as well as adverse cardiac and cerebrovascular events.…”
Section: Hypertension and Migraine -Gardener Et Almentioning
confidence: 99%